2005
DOI: 10.1002/rcm.1838
|View full text |Cite
|
Sign up to set email alerts
|

Acetonitrile/water gas‐phase reaction products observed by use of atmospheric pressure chemical ionization: adducts formed with sulfonamides

Abstract: Electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) are the two most common mass spectrometric ionization methods used in the pharmaceutical industry. However, APCI analysis can sometimes lead to ambiguity in compound characterization and quantitation due to gas-phase reactions occurring between acetonitrile and water in the plasma, and between these plasma-generated compounds and the analyte. During the analysis of various sultams and sulfonamides we observed signals correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, reduction of nitro compounds and aromatic amines has been observed 24, 25. Ion molecule reactions with acetone,26 acetonitrile,27, 28 and nitrogen29 also occur in APCI plasmas. In the case of nitro reduction the plasma is surface‐assisted, and can be minimized by avoiding protic solvents, by the use of clean heated probe liners and, surprisingly, the use of higher heated nebulizer temperatures (>500°C).…”
Section: Resultsmentioning
confidence: 82%
“…For example, reduction of nitro compounds and aromatic amines has been observed 24, 25. Ion molecule reactions with acetone,26 acetonitrile,27, 28 and nitrogen29 also occur in APCI plasmas. In the case of nitro reduction the plasma is surface‐assisted, and can be minimized by avoiding protic solvents, by the use of clean heated probe liners and, surprisingly, the use of higher heated nebulizer temperatures (>500°C).…”
Section: Resultsmentioning
confidence: 82%
“…Nevertheless, it has been shown that gas-phase reduction of ACN in the presence of [16,17]. Data interpretation of these unusual ions may require additional experimental data while H/D exchange methodologies can be applied to confirm these gas-phase reaction products.…”
Section: H/d Exchange Lc-ms For Probing Gas-phase Reaction Ion Structmentioning
confidence: 98%
“…One of the reasons for this finding is the practical problems observed in the corona needle when ACN is used as organic modifier, which contributes to lower ionisation efficiency. Besides, Ross et al [17] have recently reported that APCI analyses sometimes lead to ambiguity on compound characterisation and quantification since a new reactive species has been observed for certain classes of compounds when ACN/ water is used as the solvent system. At present, ESI mode is being most widely used in conjunction with LC in our research laboratories.…”
Section: Practical Considerationsmentioning
confidence: 99%